A PRELIMINARY OBSERVATION ON AN EXPLICIT ANTIMICROBIAL ACTION OF MANGROVE PLANTS ON PSEUDOMONAS AERUGINOSA: Antimicrobial action of mangrove plants - TAMANNA SULTANA,; ARUP KUMAR MITRA,; SATADAL DAS, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Due to emerging drug-resistant microorganisms throughout the world, newer antimicrobial agents should be looked for. Plants are enriched with different bioactive chemicals. In this study, we searched antibacterial activities of some mangrove plant extracts against Pseudomonas aeruginosa, Staphylococcus aureus, and Escherichia coli. Methods: In the present study, the antimicrobial activity of the leaves of Bruguiera gymnorhiza, Excoecaria agallocha, Avicennia alba, and Aegialitis rotundifolia was evaluated against a few reference pathogenic bacterial strains, namely, P. aeruginosa ATCC 27853, E. coli ATCC 25922, S. aureus ATCC 29213, and multidrug-resistant bacterial strains E. coli extended-spectrum beta-lactamases strain. Aqueous, ethanolic, methanolic, and dimethyl sulfoxide (DMSO) extracts were studied. The antimicrobial activities of the organic solvent extracts on the various test microorganisms were investigated using agar well diffusion technique followed by determination of minimum inhibitory concentration values by serial dilution in a microtiter plate. Results: Ethanol and DMSO extracts of B. gymnorhiza exhibited promising antimicrobial activity followed by extracts of A. alba and E. agallocha. Among all microorganisms studied, P. aeruginosa ATCC 27853 showed significant growth inhibition with ethanol and DMSO extracts. Conclusion: Extracts of some mangrove plants, particularly, B. gymnorhiza showed very good antimicrobial activities against common microbial agents causing human infections and in general mangrove plants appear to act better on P. aeruginosa.